Early surgical menopause and its correlates: A case series from a tertiary healthcare institute in a tribal area of Jharkhand, India - Priyanka Rai; Sudip Bhattacharya; Manish Raj; Swapnil Bala (Wolters Kluwer Medknow Publications, 2023)
In India, unjustified and mass hysterectomy is an alarming issue in rural and semi-urban areas. Fear of cancer and reiterating the idea that uterus removal will alleviate unrelated somatic issues are two methods used to persuade women to have the surgery. It becomes easier to counsel them for hysterectomy, especially when they belong to the rural population, come from lower socioeconomic strata, are young and illiterate, and do nothing for their livelihood. Many patients from the Santhal Pargana division (tribal region) came to gynecology Out Patient Department after having a hysterectomy without any medical indication at an age below 30 years to cure their common symptoms such as lower abdominal pain and vaginal discharge, and this is our major concern from them. We have taken three patients for this case series to highlight this problem at the community level. Unfortunately, the adverse health consequences of early loss of ovarian function accelerate the menopause state, affect multiple systems including cardiovascular, neurological, bone, and connective tissues, and, most importantly, affect the quality of life owing to vasomotor symptoms, mood, sleep, and sexual function. This case series emphasizes the serious complications of unnecessary hysterectomies and problems and gender inequities in the healthcare system for poor women.